Influence of Spanking as a Corrective and Preventive Technique on Students’ Misbehaviour in Public Secondary Schools in Ogbaru Local Government Area of Anambra State, Nigeria (Journal of Guidance and Counselling Studies, 2024)
There has been an under tone about use of spanking as disciplinary technique for students’ classroom misbehaviours. Notwithstanding, it seems an effective chastening for students’ classroom misbehaviours and still acceptable across cultures and nations of the world. In view of the varied opinions about this phenomenon, there is a need to empirically investigate the perception of teachers who are the classroom managers on the influence of spanking as a chastening for misbehaviour among secondary students. This study adopted a descriptive survey research design. The population of this study consisted of 288 teachers from 10 public secondary schools in Ogbaru  Local Government Area Of Anambra State, Nigeria. The sample of the study comprised of 45 teachers selected using simple random sampling. A 13-item questionnaire titled “Spanking a corrective chastening for students’ misbehaviour questionnaire (SACCFSMQ)” developed by the researchers was the instrument used for data collection. The instrument was validated by five experts in educational Management and Policy at Nnamdi Azikiwe University, Awka. The reliability of the questionnaire was established by sharing the questionnaire to a sample of 15 teachers away from the area of the study. The scores obtained were computed using Cronbach Alpha statistics which gave internal consistency reliability value of 0.78, showing that the questionnaire was reliable for conducting the study. Data collected were analyzed using mean scores rated at 2.50.  From the findings of this study it was revealed that spanking is a corrective and preventive classroom management technique for students’ misbehaviours.